Friday
March 24, 2017

Post a New Question

Posted by on Saturday, January 28, 2012 at 2:16pm.

3/(2m+4)= 1/(m+2)- 2

  • College Math - , Saturday, January 28, 2012 at 4:03pm

    m=4

  • College Math - , Monday, January 30, 2012 at 6:16pm

    3/(2m+4) = 1/((m+2)-2)

    STEP 1:

    3*((m+2)-2) = 1*(2m+4)

    STEP 2:

    3m+6-6 = 2m+4

    STEP 3:

    3m = 2m+4 ----> 3m-2m = 4

    FINAL

    m = 4

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question